2017
DOI: 10.1002/2017ja024556
|View full text |Cite
|
Sign up to set email alerts
|

Flux Enhancements of > 30 keV Electrons at Low Drift Shells L < 1.2 During Last Solar Cycles

Abstract: We present results of statistical analysis of enhancements of >30 keV electrons observed by the NOAA/POES satellites during solar cycles 23 and 24 (1998–2016) at low drift shells L < 1.2, so‐called forbidden zone. We collected 1,750 days (~25% of the total time) when fluxes of the forbidden energetic electrons (FEE) exceeded 103 (cm2 s sr)−1. We found 530 days, when FEE fluxes reached high intensity from 104 up to 107 (cm2 s sr)−1. It was found that the FEE enhancements were observed mostly often at the declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 47 publications
8
31
0
2
Order By: Relevance
“…Note that enhancements in 93 the forbidden zone were first reported in 1960s (Krasovskii et al, 1961;Savenko et al, 1962;94 Heikilla, 1971), however, the conclusions were unconvincing due to the scarce information (see 95 Paulikas, 1975 for a review). The recent statistical study of electron enhancements in the 96 forbidden zone showed that the injections below the inner zone can also occur during 97 geomagnetically quiet conditions (Suvorova, 2017). This fact is consistent with the recent 98 finding of "quiet" injections in the inner magnetosphere Zhao et al, 2017a).…”
Section: Introduction 28supporting
confidence: 74%
See 3 more Smart Citations
“…Note that enhancements in 93 the forbidden zone were first reported in 1960s (Krasovskii et al, 1961;Savenko et al, 1962;94 Heikilla, 1971), however, the conclusions were unconvincing due to the scarce information (see 95 Paulikas, 1975 for a review). The recent statistical study of electron enhancements in the 96 forbidden zone showed that the injections below the inner zone can also occur during 97 geomagnetically quiet conditions (Suvorova, 2017). This fact is consistent with the recent 98 finding of "quiet" injections in the inner magnetosphere Zhao et al, 2017a).…”
Section: Introduction 28supporting
confidence: 74%
“…geomagnetic storms was found, the FEE enhancements appeared to be necessarily associated 140 with substorm activity in some events studied (Suvorova et al, 2014;. However, 141 statistically, such a casual relationship with substorms was not confirmed (Suvorova, 2017). 142…”
Section: Introduction 28mentioning
confidence: 89%
See 2 more Smart Citations
“…The same pattern of Ni enhancements is also noticeable at midnight and predawn, especially during equinoxes. Coincidently, energetic electrons, the flux of which could be significantly intensified during geomagnetic storms, are also preferred to be detected at longitudes from Pacific to South America (Figure in Suvorova et al, ), at a local time near midnight (Suvorova, ). These coincidences bring insights into the nighttime ionization resulted in the ionospheric positive storm, which further benefits the occurrence of EPDs especially at midnight and after.…”
Section: Discussionmentioning
confidence: 99%